Review of reactor conceptual design and thermal hydraulic characteristics for heat pipe in nuclear systems - Wang, Enpei; Ren, Tingwei; Li, Lei (Frontiers in Energy Research, 2023)
Heat pipe cooled reactors (HPCRs) have broad application prospects due to their advantages, such as high power density, compact structure, lower cost, and easy modular assembly. Numerous countries have engaged in extensive research and development of HPCR conceptual designs. The heat from the reactor is removed by high temperature heat pipes (HTHPs), which generally employ alkali metals as the working fluid, such as potassium, sodium, and lithium. Understanding the thermal-hydraulic performance of HTHPs is essential for the safe and efficient operation of a reactor. Therefore, the objective of this paper is to provide a comprehensive review of HPCR conceptual designs developed by various countries in recent years. The research progress of HTHPs on flow and heat transfer performance is reviewed, with an emphasis on both transient and steady-state characteristics. Research progress, as well as the issues that need to be focused on in future research, are discussed in detail.